Increased dissolution rates of tranilast solid dispersions extruded with inorganic excipients. (3rd June 2017) - Maniruzzaman, Mohammed; Ross, Steven A.; Islam, Muhammad Tariqul; Scoutaris, Nikolaos; Nair, Arun; Douroumis, Dennis
Abstract: The purpose of this study was to evaluate the performance of Neusilin® (NEU) a synthetic magnesium aluminometasilicate as an inorganic drug carrier co-processed with the hydrophilic surfactants Labrasol and Labrafil to develop Tranilast (TLT)-based solid dispersions using continuous melt extrusion (HME) processing. Twin-screw extrusion was optimized to develop various TLT/excipient/surfactant formulations followed by continuous capsule filling in the absence of any downstream equipment. Physicochemical characterization showed the existence of TLT in partially crystalline state in the porous network of inorganic NEU for all extruded formulations. Furthermore, in-line NIR studies revealed a possible intermolecular H-bonding formation between the drug and the carrier resulting in the increase of TLT dissolution rates. The capsules containing TLT-extruded solid dispersions showed enhanced dissolution rates and compared with the marketed Rizaben ® product.